Convert -53 Fahrenheit to Celsius

What is -53 degrees Fahrenheit in Celsius? Just type in either box, and the number in the other box will be converted automatically.
Fahrenheit
Celsius
-53° Fahrenheit = -47.22° Celsius
(rounded to 4 digits)
How hot is -53 degrees Fahrenheit? How cold? Convert between Fahrenheit and Celsius.
More temperatures starting with -53 degrees in Fahrenheit
Note: results are rounded
-53.00 °F = -47.22 °C -52.75 °F = -47.08 °C -52.50 °F = -46.94 °C -52.25 °F = -46.81 °C
-52.99 °F = -47.22 °C -52.74 °F = -47.08 °C -52.49 °F = -46.94 °C -52.24 °F = -46.80 °C
-52.98 °F = -47.21 °C -52.73 °F = -47.07 °C -52.48 °F = -46.93 °C -52.23 °F = -46.79 °C
-52.97 °F = -47.21 °C -52.72 °F = -47.07 °C -52.47 °F = -46.93 °C -52.22 °F = -46.79 °C
-52.96 °F = -47.20 °C -52.71 °F = -47.06 °C -52.46 °F = -46.92 °C -52.21 °F = -46.78 °C
-52.95 °F = -47.19 °C -52.70 °F = -47.06 °C -52.45 °F = -46.92 °C -52.20 °F = -46.78 °C
-52.94 °F = -47.19 °C -52.69 °F = -47.05 °C -52.44 °F = -46.91 °C -52.19 °F = -46.77 °C
-52.93 °F = -47.18 °C -52.68 °F = -47.04 °C -52.43 °F = -46.91 °C -52.18 °F = -46.77 °C
-52.92 °F = -47.18 °C -52.67 °F = -47.04 °C -52.42 °F = -46.90 °C -52.17 °F = -46.76 °C
-52.91 °F = -47.17 °C -52.66 °F = -47.03 °C -52.41 °F = -46.89 °C -52.16 °F = -46.76 °C
-52.90 °F = -47.17 °C -52.65 °F = -47.03 °C -52.40 °F = -46.89 °C -52.15 °F = -46.75 °C
-52.89 °F = -47.16 °C -52.64 °F = -47.02 °C -52.39 °F = -46.88 °C -52.14 °F = -46.74 °C
-52.88 °F = -47.16 °C -52.63 °F = -47.02 °C -52.38 °F = -46.88 °C -52.13 °F = -46.74 °C
-52.87 °F = -47.15 °C -52.62 °F = -47.01 °C -52.37 °F = -46.87 °C -52.12 °F = -46.73 °C
-52.86 °F = -47.14 °C -52.61 °F = -47.01 °C -52.36 °F = -46.87 °C -52.11 °F = -46.73 °C
-52.85 °F = -47.14 °C -52.60 °F = -47.00 °C -52.35 °F = -46.86 °C -52.10 °F = -46.72 °C
-52.84 °F = -47.13 °C -52.59 °F = -46.99 °C -52.34 °F = -46.86 °C -52.09 °F = -46.72 °C
-52.83 °F = -47.13 °C -52.58 °F = -46.99 °C -52.33 °F = -46.85 °C -52.08 °F = -46.71 °C
-52.82 °F = -47.12 °C -52.57 °F = -46.98 °C -52.32 °F = -46.84 °C -52.07 °F = -46.71 °C
-52.81 °F = -47.12 °C -52.56 °F = -46.98 °C -52.31 °F = -46.84 °C -52.06 °F = -46.70 °C
-52.80 °F = -47.11 °C -52.55 °F = -46.97 °C -52.30 °F = -46.83 °C -52.05 °F = -46.69 °C
-52.79 °F = -47.11 °C -52.54 °F = -46.97 °C -52.29 °F = -46.83 °C -52.04 °F = -46.69 °C
-52.78 °F = -47.10 °C -52.53 °F = -46.96 °C -52.28 °F = -46.82 °C -52.03 °F = -46.68 °C
-52.77 °F = -47.09 °C -52.52 °F = -46.96 °C -52.27 °F = -46.82 °C -52.02 °F = -46.68 °C
-52.76 °F = -47.09 °C -52.51 °F = -46.95 °C -52.26 °F = -46.81 °C -52.01 °F = -46.67 °C